A STUDY ON THE FACTORS CAUSING STUDENTS’ DIFFICULTIES IN UNDERSTANDING READING TEXT AT ELEVENTH GRADE OF SMAN IT SYECH WALID THAIB SHALEH INDRAGIRI SUNGAI ILIRAN - Lisna Sonia; Melda Yeni; Felci Tria Sauhana (J-Shelves of Indragiri (JSI), 2024)
The problem of this research was the tenth-grade students of Eleventh Grade of SMAN Islam Terpadu Syech Walid Thaib Shaleh Indragiri Sungai Iliran feel difficult to answer some questions in reading. Therefore, the purpose of this research is to know “factors causing students difficulties in understanding Reading Text”. This research was descriptive quantitative research. The researcher was distributing questionnaire to 20 respondents to answer the purpose above. The sample was taken by using total sampling, because the sample is limited. After collecting the data, the researcher found that there are four factors causing students difficulties in understanding reading text at Eleventh Grade of SMAN Islam Terpadu Syech Walid Thaib Shaleh Indragiri. They are feeling bored and lazy in reading, cannot use the leisure time maximally for reading, lack of English book at school and uninteresting teaching learning process.